2020
DOI: 10.1088/1475-7516/2020/03/053
|View full text |Cite
|
Sign up to set email alerts
|

A search for cosmogenic neutrinos with the ARIANNA test bed using 4.5 years of data

Abstract: The primary mission of the ARIANNA ultra-high energy neutrino telescope is to uncover astrophysical sources of neutrinos with energies greater than 10 16 eV. A pilot array, consisting of seven ARIANNA stations located on the surface of the Ross Ice Shelf in Antarctica, was commissioned in November 2014. We report on the search for astrophysical neutrinos using data collected between November 2014 and February 2019. A straight-forward template matching analysis yielded no neutrino candidates, with a signal effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 52 publications
(119 reference statements)
0
73
0
Order By: Relevance
“…We also plot the projected trigger-level single-event sensitivity (TL SES) for the five-station ARA5 array by 2022 as a black-dashed curve. Also shown are the latest limits and flux measurements from IceCube [20,45], Auger [21] (rescaled with decade-wide bins and for all-flavors), ANITA [23] (rescaled with decade-wide bins), and ARIANNA [24]. Shown for comparison are several benchmark cosmogenic neutrino flux models [13,16,50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also plot the projected trigger-level single-event sensitivity (TL SES) for the five-station ARA5 array by 2022 as a black-dashed curve. Also shown are the latest limits and flux measurements from IceCube [20,45], Auger [21] (rescaled with decade-wide bins and for all-flavors), ANITA [23] (rescaled with decade-wide bins), and ARIANNA [24]. Shown for comparison are several benchmark cosmogenic neutrino flux models [13,16,50].…”
Section: Resultsmentioning
confidence: 99%
“…As such, the active volumes of the instruments required to detect this UHE flux must necessarily approach the scale of 100 km 3 water equivalent. Several experiments are operating or under construction to reach this high-energy flux, including IceCube [20], Pierre Auger [21], NuMoon [22], ANITA [23], ARIANNA [24], GRAND [25], and ARA [26], which is the focus on this work.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in [34], we have studied the possibility that the cosmogenic neutrino flux suffers from a measurable depletion (called the absorption effect) observable in future experiments, due to the presence of active-sterile secret neutrino interactions. In particular, in the scheme of one active neutrino and one sterile, we have shown that the absorption effect is maximal for energies around 10 9-10 GeV, and it could be observed at experiments like GRAND [35] and ARIANNA [36].…”
Section: Introductionmentioning
confidence: 82%
“…The detection of ultra-high-energy (UHE) neutrinos is a key to solve the 100-year-old mystery of the origin of cosmic rays and one of the crucial milestones for astroparticle physics [1]. The only cost-efficient way to measure these UHE neutrinos above 30 PeV of energy is via a sparse array of radio antenna stations installed, for instance, in the Artic or Antarctic ice [2][3][4][5]: A neutrino interaction in the ice generates a few-nanoseconds long radio flash that can be detected from kilometer-long distances. Because of the small flux, no UHE neutrino has been observed yet, but the technology has already been shown to work reliably with small test-bed arrays.…”
Section: Introductionmentioning
confidence: 99%